EFL Students’ Perspectives of Anxiety in Online Speaking Class - Firda Alvina Maharani; Tusino; Juita Trina (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2026)
Speaking anxiety is one of the most common challenges faced by English as a Foreign Language (EFL) students, particularly in online learning environments where interaction is mediated by technology. Although many studies have examined foreign language anxiety, limited research has explored students’ perspectives on speaking anxiety specifically in online speaking classes and the strategies they use to manage it. This study aims to investigate EFL students’ perspectives on speaking anxiety in online speaking classes and to identify the strategies they use to cope with this anxiety. This research employed a qualitative approach using semi-structured interviews with 10 EFL students who had experience participating in online speaking classes. The interview data were analyzed using thematic analysis to identify common patterns and themes related to students’ experiences. The findings reveal that speaking anxiety in online classes is influenced by several factors, including linguistic limitations, technical challenges such as unstable internet connections and audio problems, and psychological factors such as nervousness and fear of making mistakes. The study also found that students use various strategies to manage their anxiety, including digital support tools, preparation and practice strategies, and psychological coping strategies. These findings highlight the importance of creating supportive online speaking environments and providing opportunities for preparation and technological support to help students manage speaking anxiety and improve their confidence in English communication.